Developing a top talent readiness model for public service institution: A soft systems methodology (SSM) approach - Wang, Henny; Maarif, Mohammad Syamsul; Zulbainarni, Nimmi; Kuswanda, Harri (Edelweiss Applied Science and Technology, 2025)
In today’s dynamic era of change, public service institutions must maintain a competitive advantage to ensure sustainable performance. This advantage can be achieved by delivering high-quality public services, supported by talented employees. However, developing top talent is no simple task; it requires an approach that is not only systematic but also aligned with the organization’s evolving dynamics. This study employs Soft Systems Methodology (SSM) to develop a conceptual model for top talent readiness in public service institutions, through BPJS Ketenagakerjaan as a case study. SSM is applied to explore various stakeholder perspectives and to understand the complexities within the top talent management system. The findings indicate that the success of this model depends on full support from top management, the ability to accurately identify key positions, a clear and objective talent identification process, and the integration of career planning and individual development with the organization’s overall strategy. Additionally, the study highlights that the approach based on The Performance-Competence-Credibility framework can serve as an alternative method for top talent identification, complementing existing frameworks such as the Nine-Box Talent Grid. These insights provide valuable guidance for public service institutions in designing a more effective and sustainable top talent management system.